An EWMA monitoring scheme with a single auxiliary variable for industrial processes. (December 2017) - Sanusi, Ridwan A.; Riaz, Muhammad; Adegoke, Nurudeen A.; Xie, Min
Highlights: An EWMA-type scheme, with a single auxiliary variable, is proposed. The ratio mean estimator is used to improve the performance of the classical EWMA chart for monitoring location parameter. The study shows that the proposed chart outperforms its existing counterparts. A real-life industrial example is provided. Abstract: When using control charts to monitor manufacturing processes, Shewhart control chart is known to be useful for detecting transient shifts, while the EWMA and CUSUM charts are useful for detecting persistent shifts. The efficiency of EWMA chart in monitoring location parameter can be improved by using an auxiliary variable that is closely related to the variable of interest. In this paper, an EWMA-type scheme using ratio estimator is developed to further increase the effectiveness of the classical EWMA chart in monitoring the location parameter. The proposed procedure outperforms the classical EWMA and even the mixed EWMA-CUSUM chart, especially when there is a strong positive relationship between the variable of interest and the auxiliary variable. Finally, a real data set is used to show the implementation procedures of the proposed chart.